Basque cinema a cultural and political history - Stone, Rob; Rodríguez, María Pilar 1964- (London I.B. Tauris, 2015)
This book is the definitive study of Basque cinema, revealing how film has always been a vital medium for articulating the Basque region's unique identity and politics.
Includes bibliographical references (pages 225-236) and index.
Keywords: Motion pictures -- Spain -- País Vasco -- History